From the history of collection, publication, comprehension of abaza fairy-tale prose - Lilya A. Borokova (Кавказология)
The article recreates the history of the collections, writings and publications of Abaza fairy tales from 1929 to the present time. In this regard, the activities of A.N. Genko, T.Z. Tabulov, K.V. Lomtatidze, V.B. Tugov, V.N. Meremkulov and others are highlighted. The question is raised considering the need to bring together the entire existing body of folklore material, systematize it and reissue it in a separate series in several volumes, broken down by genre. The article also traces the study of Abaza fairy tale prose in the works of V.B. Tugov, V.N. Meremkulov, P.K. Chekalov, the contribution of each scientist to the formation of national folklore is briefly outlined. Such comprehension allows us to draw a line under the work done to date and, relying on the existing scientific base, to continue the modern study of national folklore.